Flow through a helical pipe with rectangular cross-section - Alam, Md Mahmud; Begum, Delowara; Yamamoto, K (Journal of Naval Architecture and Marine Engineering, 2008)
The effects of torsion, aspect ratio and curvature on the flow in a helical pipe of rectangular cross- section are studied by introducing a non-orthogonal helical coordinate system. Spectral method is applied as main tool for numerical approach where Chebyshev polynomial is used. The numerical calculations are obtained by the iterative method. The calculations are carried out for 0â¤ Î´ â¤0.02, 1â¤ Î» â¤ 2.85, 1â¤ Î³ â¤2.4, at Dn = 50 & 100 respectively, where d is the non-dimensional curvature, l the torsion parameter, g the aspect ratio andÂ Dn the pressure driven parameter (Dean number). DOI: http://dx.doi.org/10.3329/jname.v4i2.991 Â Journal of Naval Architecture and Marine Engineering Vol.4(2) 2007 p.99-110